(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Modern science has been marred by lingering problems and consequences, as twentieth-century critics like Theodor Adorno and Seyyed Hossein Nasr argued that modern science has been emptied of spiritual values and increasingly disconnected from ethical religious concerns. As a result, most scientists adhere to the dichotomy between science and religion, implying not only distinction, but also separation and contradiction. Equally problematic is the widely held, but naïve, view that science is neutral and value-free, has no human, economic, political, military, national, industrial or commercial interests. In the wake of realization that modern science could be harmful and detrimental to the minds and lives of Muslim. Calls for Islamization was launched across the Muslim world from Virginia to Casablanca. This article aims to assess the idea of Islamization of contemporary science as espoused and elaborated by Imam Suprayogo, a former rector of the State Islamic University (UIN) in Malang, Indonesia. Based on library research, this study found that Imam Suprayogo’s idea of Islamization prescribes integration of science and religion to eradicate the long-held dichotomy between the two, particularly between scientific claims and Islamic doctrines. Imam Suprayogo also proposed to reconstruct a religious scientific paradigm by introducing the “tree of knowledge” and launching the “Tarbiyah Ulul Albab” (education of the Intelligentsia) which has been implemented during his term in an attempt to transform UIN Malang into an Islamic educational institution that teaches both science and religion while at the same time projecting the Islamic values. Ilmu pengetahuan modern saat ini, telah dirusak oleh sejumlah masalah dan konsekuensi yang tidak diinginkan, sebagaimana kritikus abad kedua puluh seperti Theodor Adorno dan Seyyed Hossein Nasr menyatakan bahwa ilmu pengetahuan modern telah dikosongkan dari nilai-nilai spiritual dan terputus dari masalah etika keagamaan. Akibatnya, sebagian besar ilmuwan menganut dikotomi antara ilmu dan agama, hal tersebut tidak hanya perbedaan, tetapi juga pemisahan dan kontradiksi di antara keduanya. Masalah yang sama datang dari pandangan secara luas, tetapi naif, bahwa ilmu itu netral dan bebas nilai, tidak memiliki kepentingan manusia, ekonomi, politik, militer, nasional, industri atau komersial. Tanpa disadari bahwa ilmu pengetahuan modern bisa berbahaya dan merugikan pikiran serta kehidupan Muslim. Adapun seruan untuk Islamisasi telah diluncurkan ke seluruh dunia Muslim dari Virginia hingga Casablanca. Artikel ini bertujuan untuk mengkaji gagasan Islamisasi ilmu pengetahuan kontemporer sebagaimana dianut dan dielaborasi oleh Imam Suprayogo, mantan rektor Universitas Islam Negeri (UIN) Malang, Indonesia. Berdasarkan studi pustaka, penelitian ini menemukan bahwa gagasan Islamisasi Imam Suprayogo mengatur integrasi ilmu dan agama untuk menghapus dikotomi yang telah lama ada di antara keduanya, khususnya antara klaim ilmiah dan doktrin Islam. Imam Suprayogo juga mengusulkan untuk merekonstruksi paradigma keilmuan agama dengan memperkenalkan “pohon ilmu” serta meluncurkan program “Tarbiyah Ulul Albab” yang telah dilaksanakan selama istilahnya dalam upaya mentransformasi UIN Malang menjadi lembaga pendidikan Islam yang mengajarkan ilmu pengetahuan dan agama sekaligus memproyeksikan nilai-nilai Islam.